Politeness Strategies in EFL Classroom Context: Avoiding Future Conflict and Maintain the Harmony of Diversity - Elita Sembiring; Srisofian Sianturi (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2019)
The research aims to investigate the politeness in language and action by students of Letters Faculty at Methodist University. Seeing the students from different etnic, religion, and culture, should be understanding and well manage to avoid future conflict and maintain the harmony of diversity among them. The research was done in the fifth-semester Cross Cultural Understanding class of Letters Faculty, The Methodist University of Indonesia. The researchers used a qualitative approach by observing the activities of students and recording their utterances during responding to the point of view. The result shows that the students applied the four types of politeness strategies in responding to context of avoiding conflict and maintain the harmony. The types are bald on record strategy, positive strategy, negative strategy and off record strategy. From the four types of politeness strategies, bald on record strategy is dominantly used by students. It is due to the students have a similar position, and it seems that no distance between them. All the communications are between students to students. For a reason, saying something directly and to the point are frequently used. Being polite should be in words and actions. From the research, students are polite in words but not in action. .